Abnormal gene and protein expression of inflammatory cytokines in the postmortem brain of schizophrenia patients - Pandey, Ghanshyam N.; Rizavi, Hooriyah S.; Zhang, Hui; Ren, Xinguo (Schizophrenia research, 2018)
Immune function abnormalities have been implicated in the pathophysiology of schizophrenia (SZ). This is primarily based on the observation that the levels of proinflammatory cytokines are significantly increased in the serum of SZ patients compared with normal control (NC) subjects. However, it is not known if similar cytokines abnormalities are also present in the brain of SZ patients. To further examine the involvement of inflammatory cytokines in the brain of SZ patients, we determined the protein and mRNA levels of TNF-α, IL-1β, IL-2, IL-6, IL-8, IL-10, IL-13, LTA and IL-1RA in the prefrontal cortex (PFC, Brodmann area 9) of SZ patients. We found that the protein and mRNA expression levels of the cytokines TNF-α and IL-6 are significantly increased and those of IL-10 are significantly decreased in the PFC of SZ patients. No difference in the protein and mRNA levels of IL-1β, IL-13, and IL-1RA was observed between SZ patients and NC subjects. The protein expression levels of IL-8 were significantly decreased and those of LTA were significantly increased in SZ patients, but no significant difference in the mRNA levels of IL-8 and LTA was observed between SZ patients and NC subjects. The levels of IL-2 were undetectable or very low in the postmortem brain of either SZ or NC subjects. These results suggest abnormalities of specific pro- and anti-inflammatory cytokines in the postmortem brain of SZ patients. These observations may have important implications in understanding the role of inflammatory cytokines in the pathophysiology of SZ.